Implementasi master strategi dalam menciptakan nilai publik pada PDAM TKR Kabupaten Tangerang - Arsid Arsid; Ida Widianingsih; Heru Nurasa; Entang Adhy Muhtar (Publisia: Jurnal Ilmu Administrasi Publik, 2019)
The main problem faced by PDAM TKR Tangerang Regency is the low coverage of drinking water services for domestic customers or the community. Whereas services for non-domestic customers such as companies and apartments, Tangerang TKR PDAM is considered to have provided good and optimal services. The service provided by the Tangerang Regency TKR PDAM is done unevenly. This problem can be found in the difference in service quality between domestic and non-domestic consumers. This study focuses on the problem of less than optimal service to domestic customers by the Tangerang TKR PDAM. Public value theory by Mark Moore becomes the basic theory used to measure the success of a company in providing good and optimal service to the community. Company achievements are assessed in terms of service, results and trust. The strategy needed to realize this public value is the Strategy Master initiated by Higgins which includes corporate strategy, business strategy, functional strategy and enterprise strategy. This study recommends that to realize a good and optimal Public Value, Tangerang Regency TKR PDAM is deemed necessary to use the Strategy Master in its entirety and comprehensively in an effort to serve the community as domestic customers.DOI: https://doi.org/10.26905/pjiap.v4i1.2411